2021
DOI: 10.1128/mbio.02344-21
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Electron Uptake by Methanosarcina acetivorans during Direct Interspecies Electron Transfer

Abstract: The conversion of organic matter to methane plays an important role in the global carbon cycle and is an effective strategy for converting wastes to a useful biofuel. The reduction of carbon dioxide to methane accounts for approximately a third of the methane produced in anaerobic soils and sediments as well as waste digesters.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 65 publications
7
48
0
Order By: Relevance
“…At least five different cyt c proteins are encoded in the M. acetivorans genome and these proteins contain between one and seven heme-binding motifs ( Holmes et al, 2019 ). Recent studies have even proposed distinct roles for some of these cyt c proteins in intracellular electron transport during methanogenesis ( Wang et al, 2011 ; Li et al, 2006 ; Schlegel et al, 2012 ; Ferry, 2020 ), extracellular electron transfer ( Holmes et al, 2019 ), as well as direct interspecies electron transfer between M. acetivorans and bacterial strains like Geobacter metallireducens ( Holmes et al, 2021 ). Thus, M. acetivorans is not only an ideal candidate to dissect the biogenesis of cyt c in Archaea but also to functionally characterize the role of cyt c in various electron transfer processes that have ramifications on global carbon cycling as well as on the formation of microbial communities in anoxic environments.…”
Section: Introductionmentioning
confidence: 99%
“…At least five different cyt c proteins are encoded in the M. acetivorans genome and these proteins contain between one and seven heme-binding motifs ( Holmes et al, 2019 ). Recent studies have even proposed distinct roles for some of these cyt c proteins in intracellular electron transport during methanogenesis ( Wang et al, 2011 ; Li et al, 2006 ; Schlegel et al, 2012 ; Ferry, 2020 ), extracellular electron transfer ( Holmes et al, 2019 ), as well as direct interspecies electron transfer between M. acetivorans and bacterial strains like Geobacter metallireducens ( Holmes et al, 2021 ). Thus, M. acetivorans is not only an ideal candidate to dissect the biogenesis of cyt c in Archaea but also to functionally characterize the role of cyt c in various electron transfer processes that have ramifications on global carbon cycling as well as on the formation of microbial communities in anoxic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Holmes et al (2021) proposed a new model of DIET methanogenic pathways, which was confirmed in the defined co-culture of G. metallireducens and Methanosarcina acetivorans . Multiheme membrane-bound c-type cytochrome A (MmcA) in M. acetivorans played an important role in electron transfer.…”
Section: Challenges Of Direct Interspecies Electron Transfer In Anaer...mentioning
confidence: 84%
“…GAC did not make the co-culture system with MmcA-deficient strains produce methane rapidly, which was mainly because that MmcA was embedded in the cell membrane of M. acetivorans ( Ferry, 2020 ). Researches show that MmcA may exchange electrons with MP or rhodobacter nitrogen (Rnf) complex ( Suharti et al, 2014 ; Ferry, 2020 ; Holmes et al, 2021 ). The function of the Rnf is to accept electrons to produce the reduced ferredoxin, which is required for the first step in the reduction of CO 2 ( Holmes et al, 2021 ).…”
Section: Challenges Of Direct Interspecies Electron Transfer In Anaer...mentioning
confidence: 99%
See 2 more Smart Citations